Desertion the teaching profession: perspective of Chilean public-school teachers (Práxis Educativa, 2025)
The aim was to know the perception of teachers of public schools in a region of central-southern Chile regarding the desertion of the profession. The qualitative methodology was used with a descriptive hermeneutic phenomenological design. The data collection was carried out through semi-structured interviews, based on the primary categories raised in advance. The sample was composed of nine high school teachers from who currently work at public-managed schools. The results show that teachers' mental health is impaired by various causes, mainly by work stress and social relationships. On the other hand, financial retribution is another factor mentioned by the teachers interviewed. It is concluded that educational policies should be oriented to the protection of educators by ensuring an appropriate work environment for their mental and physical health.Keywords: Teachers. Teachers’ drop-out. Mental health.